Life cycle energy of vehicles on lightweighting and alternative powertrain strategies—A review - Helena Monteiro; Rita Alonso; Margarida Gonçalves; Muriel Iten; Nídia S. Caetano (Energy Reports, 2022)
To improve vehicles environmental performance, different strategies have been explored namely to reduce the use stage energy. In order to avoid problem shifting, a life cycle perspective should be used to compare alternative solutions. This paper aims to compare existing studies focused on life cycle energy (LCE) of vehicles to analyze the impacts and benefits regarding two trending improvement strategies: lightweight materials and alternative powertrain selection. A Literature review was performed to systematize quantitatively the LCE results of different studies (e.g. presented among figures, tables, and literature text). The LCE results were compiled and normalized for the same driving distance, 200 000 km, per life cycle stage. Moreover, the study discusses research findings on the application of the two strategies to improve overall vehicles’ LCE. As lightweight materials have generally higher embodied energy, the material selection is highly influenced by end-of-life scenarios. It was observed that carbon/glass fiber composites generally have the highest embodied energy, being a preferable option for vehicles that last longer driving distances. Innovative powertrains sourced by renewable energy sources, electric mixes, can significantly reduce vehicles’ LCE use stage, counteracting the benefit of lightweight design. Thus, the benefit of both strategies should be studied together.